Strategy to Internalizing Religious Moral Values in the Learning Process in Higher Education - Samsul Susilawati; A Fatah Yasin; Aniek Rahmaniah; Abdulloh Chakim; Triyo Supriyanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to describe strategies for internalizing moral and religious values in the learning process in universities. This research is descriptive research with a qualitative approach. The research subjects were lecturers at the Islamic Education Department at the State Islamic University of Maulana Malik Ibrahim Malang, the University of Muhammadiyah Malang, and the Islamic University of Malang. Data were collected through interviews, observations, and documents. The triangulation technique assessed confidence data. The results showed that the strategies for internalizing moral and religious values in the learning process include: modelling, analyzing actual problems in society, developing contextual educational values, and strengthening the moral values that students have. The Internalization Strategy of Religious Moral Values in the Learning process carried out in the three PTKIS shows that moral education is conveyed in the form of cognitive moral values and is already at the stage of internalizing values by carrying out the direct practice of moral values in education. Student life and activities every day. It is hoped that from the internalization of moral education, the character of moderate Muslims who are friendly and tolerant will be built.